Diseño y evaluación mediante simulación de un prototipo de máquina extractora de mesocarpio para la granadilla (2020)
The research project describes the design and evaluation by simulation of a prototype mesocarp extraction machine for granadilla; a team that is made up of a roller abrasion system whose function is to remove the granadilla shell until obtaining the membrane or mesocarp, so that it subsequently passes to the section of the machine known as a centrifuge where the pulp and seed are separated. According to the research carried out and the calculations carried out, it was obtained that the diameter of the centrifuge is 300 mm with a height of 500 mm, contemplating that 8 granadillas can be processed along the drum, being approximately 800 grams. of the product that can be maneuvered; therefore it is estimated that the maximum lateral load it can bear is 10 Kg; This section of the prototype works by a motor (2 hp for rollers, 0.5 hp for rollers) that drives 1800 rpm, according to the selection made, which will be transmitted to a chain whose relationship is type 06A with chain pitch 9,525 (3/8 "); Now, the centrifuge will operate with a motor and a pulley transmission distributed in turn in two SPA-type belts for a power of 2 hp; Consequently, it is established that the prototype has two power units for each process (peeling and spinning), which simulation and analysis of results was carried out using Autodesk Inventor software, giving parametric level the viability of the prototype, within which highlights the production efficiency whose maximum capacity is 180 kg / h, each spin cycle comprises 30 kg every 10 min; It is said to be efficient and does two processes simultaneously, unlike conventional processes such as hydrolysis or manual.